2011
DOI: 10.1186/1749-8090-6-142
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump or minimized on-pump coronary surgery - initial experience with Circulating Endothelial Cells (CEC) as a supersensitive marker of tissue damage

Abstract: BackgroundOff-pump-coronary-artery-bypass-grafting (OPCAB) and minimized-extracorporeal-circulation (Mini-HLM) have been proposed to avoid harmful effects of cardiopulmonary-bypass (CPB). Controversies exist whether OPCAB is still superior in perioperative outcome. Circulating endothelial cells (CEC) are sensitive markers of endothelial damage and are significantly elevated in conventional-CPB-procedures as compared to Mini-HLM-revascularisation. Therefore, CEC might be of specific value in evaluating effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…36e38 CECs shed from the vessel wall and circulate in peripheral blood, acting as sensitive markers of endothelial damage. 39,40 It was found that silencing of lncRNA DLGAP1-AS1 led to declines in MDA concentration and CK activity, affecting the recovery of CECs. Taken together, the current study found that lncRNA DLGAP1-AS1 was highly expressed in I/R, and silencing lncRNA DLGAP1-AS1 alleviated VEC injury and inflammation by means of activating the PI3K/Akt pathway in acute lower limb I/R rats The current study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…36e38 CECs shed from the vessel wall and circulate in peripheral blood, acting as sensitive markers of endothelial damage. 39,40 It was found that silencing of lncRNA DLGAP1-AS1 led to declines in MDA concentration and CK activity, affecting the recovery of CECs. Taken together, the current study found that lncRNA DLGAP1-AS1 was highly expressed in I/R, and silencing lncRNA DLGAP1-AS1 alleviated VEC injury and inflammation by means of activating the PI3K/Akt pathway in acute lower limb I/R rats The current study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Our general findings are also consistent with those of Mazzei et al [8] who found that the release of inflammatory markers, as well as length of intensive care unit, hospital stay, complication rate and need for allogenic transfusion were similar in the OPCAB and a Mini-HLM group. Additionally, it was shown that use of modern Mini-HLM systems as compared to CCPB is associated with significantly reduced release of circulating endothelial cells (CEC) who are considered to represent a novel and hypersensitive marker of the severe intrinsic endothelial damage with detachment of endothelial cells into the blood stream caused by CCPB [35]. Recently, CEC release in Mini-HLM procedures was found to be as low as it could be shown for OPCAB procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The primary source of vWF is the vascular endothelium, which produces it without stimuli and also provides the rapid release of intracellular stores in response to other stimuli like thrombin, fibrin, and vasopressin. Wittwer et al [18] have found that increase plasma vWF levels after surgery involving CPB. During CPB, many different variables, particularly vascular endothelial injuries, can influence vWF levels.…”
Section: Discussionmentioning
confidence: 99%